Racial and Ethnic Disparities in Structural Disadvantage and Crime: White, Black, and Hispanic Comparisons - Ulmer, Jeffery T. (2012)
OBJECTIVES: The objective of this study is to advance knowledge on racial/ethnic disparities in violence and the structural sources of those disparities. We do so by extending scarce and limited research exploring the relationship between race/ethnic gaps in disadvantage and differences in violent crime across groups. METHODS: Using census place-level data from California and New York, we construct White, Black, and Hispanic “gap” measures that take as a given the existence of disparities across race/ethnic groups in structural disadvantage and crime and subsequently utilize seemingly unrelated regression models to assess the extent to which gaps in disadvantage are predictive of gaps in homicide and index violence. RESULTS: Our results suggest that (1) there is considerable heterogeneity in the size of White-Black, White-Hispanic, and Black-Hispanic gaps in structural disadvantage and crime and (2) that race/ethnic disparities in structural disadvantage, particularly poverty and female headship, are positively associated with race/ethnic gaps in homicide and index violence. CONCLUSION: In light of recent scholarship on the racial invariance hypothesis and on the relationship between structural inequality and crime, the current study demonstrates that disparities in disadvantage, particularly family structure and poverty, are important in driving racial and ethnic disparities in crime.